Suprascapular Nerve Pulsed Radiofrequency for Chronic Shoulder Pain in a Pediatric Patient - Federico Cristiani; Maria A. Hernandez (Case Reports in Anesthesiology)
Pulsed radiofrequency of the suprascapular nerve has shown efficacy in adults with chronic shoulder pain, but its use in pediatrics is relatively new. We present a case of a successful use of pulsed radiofrequency to treat refractory chronic shoulder pain in an adolescent patient. Case Report. We present a 53 kg, 14-year-old female, with a medical history of septic arthritis of the left shoulder within the first month of life leading to persisting pain during childhood. She presented with a complaint of progressive pain starting at age 12, refractory to analgesics including opioids and intra-articular injection of local anesthetic and steroids. After pulsed radiofrequency of the suprascapular nerve, significant pain relief and improvement of the range of motion was obtained. These results were maintained at the 1-, 3-, and 6-month follow-up visits with the pain being reported as mild and manageable with nonsteroidal anti-inflammatory drugs. Conclusion. There is limited data today of the use of pulsed radiofrequency for pediatric chronic pain. We successfully used this intervention in a 14-year-old patient with chronic shoulder pain extrapolating from adult experience and as a last resort after all other treatments had failed.